Design and Manufacturing of a High-Precision Sun Tracking System Based on Image Processing - Kianoosh Azizi; Ali Ghaffari (International Journal of Photoenergy)
Concentration solar arrays require greater solar tracking precision than conventional photovoltaic arrays. This paper presents a high precision low cost dual axis sun tracking system based on image processing for concentration photovoltaic applications. An imaging device is designed according to the principle of pinhole imaging, making sun rays to be received on a screen through pinhole and to be a sun spot. The location of the spot is used to adjust the orientation of the solar panel. A fuzzy logic controller is developed to achieve this goal. A prototype was built, and experimental results have proven the good performance of the proposed system and low error of tracking. The operation of this system is independent of geographical location, initial calibration, and periodical regulations.